Assessment of abnormally low tenders: a multinomial logistic regression approach. Issue 6 (2nd November 2017) - Gunduz, Murat; Karacan, H. Volkan
Abstract: This study was performed in order to reveal factors affecting abnormally low tenders (ALTs) and to minimize negative effects of them. A thorough literature review was carried out to observe past research about the reasons of and possible solutions to ALTs. A questionnaire was prepared and submitted to construction professionals to capture negative impacts of ALTs based on the interviews with experts and past literature. 430 companies responded to the questionnaire. The data analysis was carried out by the multinomial logistic regression statistical tool. Having quality control systems and restricted procedure with prequalification procurement systems were main significant factors to reduce ALTs. Based on all significant factors, recommendations were made to construction professionals and companies to reduce adverse effects of ALTs.